Analisis Minat Masyarakat terhadap Pemilihan Moda Transportasi Online: Studi pada Pengguna Grab di Salatiga - Ananditiya, Dava; Sumantri, Andar Sri; Sulistyowati, Sulistyowati (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This research aims to find out the rates, time efficiency, and service quality towards the interest of service users in using Grab’s online transportation services in the city of Salatiga. The population in this study is all customers who use Grab transportation, where the sampling technique used is non-probability sampling with a sampling type, namely quota sampling with predetermined characteristics and criteria. The analysis method used is descriptive analysis and quantitative analysis, the data is analyzed using multiple linear regression analysis with the help of (software) Statistic Package For Social Science (SPSS) Version 26. The results of this study show that variables, rates, time efficiency, and service quality have a partial effect on the interest of service users. The results of multiple linear regression analysis obtained the equation Y = 1,029 + 0.220 X1 + 0.130 X2 + 0.330 X3 + µ. From the multiple linear regression equation, it can be seen that the most dominant variable that affects the interest of service users is the quality of service with a regression coefficient of 0.330 and with the Ajustted R Squaer test of 0.522 or 52.2% of the variable variation tied to the interest of service users can be explained by the tariff-free variable, time efficiency, and service quality. While the remaining 47.8% is explained by other causes outside the variables studied. Based on the results of the research, conclusions can be drawn from the analysis of multiple linear regression and the distribution of respondents’ answers regarding independent variables (Tariff, Time Efficiency and Service Quality), which have an influence on dependent variables (Service User Interest).